2012
DOI: 10.4067/s0717-95532012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Factores Relacionados a La Calidad De Vida Y Satisfacción en Estudiantes De Enfermería

Abstract: Las universidades, en su rol de formadoras, deben proporcionar un ambiente académico que favorezca la calidad de vida (CV) de los estudiantes. Objetivo: Determinar los factores que se relacionan con la CV y Satisfacción en estudiantes de Enfermería. Material y método: Investigación transversal, descriptiva y correlacional. Realizada en estudiantes de Enfermería, Universidad de Concepción, Chile, año 2009. La muestra formada por 228 estudiantes. Se aplicó Cuestionario Calidad de Vida y Satisfacción (Q-LES-Q) y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
2
8
0
9
Order By: Relevance
“…To sum up, on the one hand the findings here confirm the results of previous studies and therefore contribute to the consolidation of the framework of variables that affect life satisfaction during youth (Barraza & Ortiz, 2012;Denegri et al, 2014;Moyano et al, 2013;Schnettler et al, 2013;Zubieta & Delfino, 2010;Zubieta et al, 2012). On the other hand they provide more specific background information in relation to the student population which can serve as a reference for decision-making in public policies and intervention in mental health.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To sum up, on the one hand the findings here confirm the results of previous studies and therefore contribute to the consolidation of the framework of variables that affect life satisfaction during youth (Barraza & Ortiz, 2012;Denegri et al, 2014;Moyano et al, 2013;Schnettler et al, 2013;Zubieta & Delfino, 2010;Zubieta et al, 2012). On the other hand they provide more specific background information in relation to the student population which can serve as a reference for decision-making in public policies and intervention in mental health.…”
Section: Discussionsupporting
confidence: 76%
“…H2: The proposed five factors structure which compose the scale will have well-adjusted with the data. , Regarding the second objective, previous studies have reported that university students assess their lives positively (Barraza & Ortiz, 2012;Domínguez-Espinoza, Salas, Contreras, & Procidano, 2011;Gómez, Villegas, Barrera, & Cruz, 2007;Martínez, 2004;Schnettler et al, 2011;Moyano, Cornejo, Carreño, & Muñoz, 2013;Schnettler et al, 2013;Zubieta & Delfino, 2010;Zubieta et al, 2012), which provides the descriptives hypothesis: (H 3 ) A level above the central point of the scale of life satisfaction by domains will be observed in university students. In relation to the third and fourth objectives, the current stateof-the-art reveals differences according to gender and socioeconomic level where women (Zubieta & Delfino, 2010;Zubieta et al, 2012) and the highest socioeconomic levels (Martínez, 2004;Zubieta & Delfino, 2010) present more positive assessments than their comparison groups, and it is therefore expected that: (H 4 ) In female university students, the level of life satisfaction by domains will be greater than in male university students.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies on factors related to the quality of life of nursing students highlight their poor satisfaction with the curriculum flexibility, which can interfere with the satisfaction of leisure needs and compromise the quality of life. 5 The QOL domain of social relationships with highest scores is related to the students' feeling of equal satisfaction with the relationship and support they receive from friends and relatives (88.4%) and their sexual life (44.2%). Added to these revelations is the fact that most students participating in the study lived with friends.…”
Section: Discussionmentioning
confidence: 99%
“…9 The training function of the university should provide a learning environment that promotes the QOL of students. 5 However, studies have shown that the QOL of nursing students has been affected by the time overload of the course and the lack of time for leisure. 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation